Percobaan Efek Foto listrik Berbasis Arduino Uno dengan LED 3 Warna sebagai Sumber Cahaya - Aris Doyan; Ayu Safitri Melita (Kappa Journal, 2022)
This study aims to create a tool that can explain the event of the photoelectric effect on a laboratory scale. So that the existence of a tool that can explain the photoelectric effect will make it easier for users to study the nature of light as a particle. This tool is designed according to its function which will find out that the photoelectric effect event is not influenced by light intensity but is influenced by the frequency of a light source and the wavelength that illuminates a metal so that electrons will move from a negative source towards a positive voltage source. In the manufacture of these tools, a photodiode is used as a light sensor where when the photodiode is illuminated by light it will cause electrons to move from the cathode to the anode and make an electric current flow. To determine the stopping voltage, a voltage is applied to the cathode where the electrons are ejected. This stopping voltage for each wavelength is different. From the ongoing data retrieval, a graphic relationship is obtained between the ADC value and the Sensor Output Voltage. Thus, it can be concluded that, First, the voltage applied to the photodiode (cathode) is different for each color spectrum. Second, the output voltage obtained for each different wavelength, the less light intensity received by the photodiode, the smaller the output voltage value. The amount of output voltage for each LED color is different because the wavelength of each color is also different so the value is not the same.